Electron scattering and effects of sources of light on photoconductivity of SnO2 coatings prepared by sol-gel - Messias, F. R.; Vega, BAV; Scalvi, LVA; Li, M. S.; Santilli, C. V.; Pulcinelli, S. H. (Elsevier B.V., 1999)
Electro-optical properties of sol-gel derived 2 mol% antimony or niobium doped tin dioxide films have been measured. The electron density has been calculated considering all the relevant scattering mechanisms and experimental conductivity data measured in the range -197 to 25 degrees C. The results support the hypothesis that both ionised impurity scattering and grain boundary scattering have comparable effects in the resistivity of coatings, for free electron density congruent to 5 x 10(18) cm(-3). We have measured variation of photoconductivity excitation with wavelength using xenon and deuterium lamp as light sources. Results show that the main band in the photoconductivity spectrum is dependent on the spectral light source emission, the excitation peak reaching 5 eV (deuterium lamp). This band is due to the recombination process involving oxygen species and photogenerated electron-hole pairs. (C) 1999 Elsevier B.V. B.V. All rights reserved.